2017
DOI: 10.1242/jcs.196139
|View full text |Cite
|
Sign up to set email alerts
|

Tension regulates myosin dynamics during Drosophila embryonic wound repair

Abstract: Embryos repair epithelial wounds rapidly in a process driven by collective cell movements. Upon wounding, actin and the molecular motor non-muscle myosin II are redistributed in the cells adjacent to the wound, forming a supracellular purse string around the lesion. Purse string contraction coordinates cell movements and drives rapid wound closure. By using fluorescence recovery after photobleaching in Drosophila embryos, we found that myosin turns over as the purse string contracts. Myosin turnover at the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 46 publications
(27 reference statements)
3
20
0
Order By: Relevance
“…The order in which cells are evicted correlates with local myosin accumulation at each cable-forming edge. This is consistent with previous findings that myosin intensity correlates with tension in wound-healing cables 36 , 37 . Furthermore, it has been suggested that a non-uniform stepwise contractility of individual edges is necessary for efficient epithelial closure during wound healing in Drosophila embryos and neural tube closure in chordates 38 , 39 .…”
Section: Discussionsupporting
confidence: 93%
“…The order in which cells are evicted correlates with local myosin accumulation at each cable-forming edge. This is consistent with previous findings that myosin intensity correlates with tension in wound-healing cables 36 , 37 . Furthermore, it has been suggested that a non-uniform stepwise contractility of individual edges is necessary for efficient epithelial closure during wound healing in Drosophila embryos and neural tube closure in chordates 38 , 39 .…”
Section: Discussionsupporting
confidence: 93%
“…1 ), and the same effect can be induced by decreasing the cleft angle ( 18 ). This interpretation is in agreement with in vivo data because cytoskeletal tension was reported to up-regulate myosin dynamics during Drosophila embryonic wound repair ( 4 ), whereby myosin activity is regulated by RhoA/Rock. Also in agreement with the data, we found previously that FN fiber tension in early ECM is up-regulated in a RhoA-dependent manner ( 25 ).…”
Section: Discussionsupporting
confidence: 91%
“…, 2011; Tojkander et al. , 2015), or from the turnover of myosin, which is reduced as tension increases (Kobb et al. , 2017).…”
Section: Modulation Of Force Generation In Actomyosin Bundlesmentioning
confidence: 99%